Young Workers and Age Discrimination: Tensions and Conflicts. (30th April 2018) - Blackham, Alysia
Abstract: Young workers occupy a particularly vulnerable position in the contemporary labour market. While this may partly be attributable to structural trends, it is also related to age discrimination, which is embedded in labour law and organisational practices. Age discrimination against younger workers raises many of the same tensions as age discrimination against older workers. This article therefore calls for a reconsideration of how we frame and conceive age discrimination law.